An analysis of factors affecting climate change adaptation strategies on maize production by household: case of Seke district - Gutu, Palmmah (Midlands State University, 2015)
Climate change has resulted in several effects which include floods, droughts and shifts in marginal agriculture systems leading to a reduction in agriculture output which has led to food insecurity in the country. Following some analysis, adaptation has been suggested as the way to combat the effects of climate change, but however, these adaptation strategies are area specific and affected by different factors thus the researcher sought to analyse the factors affecting climate change adaptation strategy by households in Seke district. The research employed a random sampling in collecting primary data and 156 questionnaires were administered randomly to household farmers. Results showed that 9 strategies were found to being used in Seke district to combat the effects of climate change of which three where found to be dominant which are minimum tillage, varying planting dates and dry and early planting. The researcher used the multinomial logit regression to analyse factors affecting the adaptation of the copying strategies. From the findings it could be concluded that the majority of the farmers are aware of climate change in the area shown by farmers’ response through different strategies. It could also be drawn that different factors have different influence on copying strategy employed by the household such as; level of education, gender and household size has a significant effect on dry and early planting, education level, age, gender and farm size has a significant effect on varying planting date strategy. Age was proved to have a positive relation to adaptation strategy though statistically insignificant. The researcher recommends that a multidisciplinary extension approach be done to increase and strengthen the adaptation capacity of the households and also promotion of some forms of education other than the well known formal education.